Once, when I asked one of my friends to write the expansion of
He wrote -
For which condition below my friend is correct?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
We know, ( a + b + c ) 3 = a 3 + b 3 + c 3 + 3 ( a + b ) ( b + c ) ( c + a )
Therefore, ( a + b + c ) 3 = a 3 + b 3 + c 3 will be true, if ( a + b ) ( b + c ) ( c + a ) = 0 ⇒ ( a + b ) ( b c + a b + c 2 + c a ) = 0 ⇒ a b c + a 2 b + c 2 a + c a 2 + b 2 c + a b 2 + b c 2 + a b c = 0 ⇒ a 2 b + a b c + c a 2 + a b 2 + b 2 c + a b c + a b c + b c 2 + c 2 a = a b c ⇒ ( a + b + c ) ( a b + b c + c a ) = a b c
So, the answer is ( a + b + c ) ( a b + b c + c a ) = a b c